RNA-binding region of Macrobrachium rosenbergii nodavirus capsid protein - Goh, Zee Hong; Syakirin Mohd, Nur Azmina; Tan, Soon Guan; Bhassu, Subha; Tan, Wen Siang (Society for General Microbiology, 2014)
White tail disease (WTD) kills prawn larvae and causes drastic losses to the freshwater prawn (Macrobrachium rosenbergii) industry. The main causative agent of WTD is Macrobrachium rosenbergii nodavirus (MrNV). The N-terminal end of the MrNV capsid protein is very rich in positively charged amino acids and is postulated to interact with RNA molecules. N-terminal and internal deletion mutagenesis revealed that the RNA-binding region is located at positions 20–29, where 80 % of amino acids are positively charged. Substitution of all these positively charged residues with alanine abolished the RNA binding. Mutants without the RNA-binding region still assembled into virus-like particles, suggesting that this region is not a part of the capsid assembly domain. This paper is, to the best of our knowledge, the first to report the specific RNA-binding region of MrNV capsid protein.